THE ROLE AND OBSTACLES OF LOCAL GOVERNMENTS IN IMPLEMENTING INFRASTRUCTURE, FACILITIES AND PUBLIC WORKS OF HOUSING AND RESIDENTIAL AREAS IN THE OGAN KOMERING ILIR AREA - Try Fitryanti; Erli Salia; Mulyadi Tanzili (Universitas Labuhanbatu, 2024)
Everyone has the right to physical and spiritual well-being, a place to live, and a good and healthy living environment. In Indonesia, this is regulated in the 1945 Constitution of the Republic of Indonesia (hereinafter referred to as the 1945 Constitution of the Republic of Indonesia) and regulated in Article 28 Paragraph H (1) of the 1945 Constitution of the Republic of Indonesia. In this research, the approach used is normative juridical or doctrinal , legal research carried out by examining library materials or secondary data as basic material for research by conducting searches on regulations related to the issues discussed. Then the problem that is analyzed and studied is the role and obstacles of the regional government in implementing infrastructure, facilities and public works for housing and residential areas in the Organ Komering Ilir area. Results: In managing infrastructure, facilities and public services in Ogan Komering Ilir Regency, the role of local government is very important. The Ogan Komering Ilir Regent's government, through the Public Housing and Settlement Service, is tasked with implementing infrastructure, facilities and public services to support the function of settlements to ensure the welfare and comfort of the people who live in Ogan Komering Ilir Regency. Then there are challenges and obstacles in the process of transferring public infrastructure and facilities from the developer to the Ogan Komering Ilir Regent Government. Although existing, sustainable and reliable management must be maintained to ensure sustainability, challenges and obstacles still remain in the provision of public infrastructure and facilities. Budget and human resources in managing housing infrastructure, equipment and public services are limited. This can affect the quality and quantity of services provided by local governments. To overcome these obstacles, planned and coordinated efforts are needed from local governments, real estate developers and local communities..Keywords: role; obstacl; facilities; housing public works; residential area.